Pregnancy in a Woman with Latent Myeloproliferative Neoplasm Induced Chronic Portal Vein Thrombosis, Portal Cavernoma, and Gastric Varices - Andréanne Durivage; Geneviève Le Templier; Annabelle Cumyn; Nadine Sauvé (Case Reports in Obstetrics and Gynecology)
Extra-hepatic portal vein thrombosis (EHPVO) represents the obstruction of the portal vein outside the liver and is not related to chronic liver disease or neoplasia. In chronic EHPVO, collateral veins and portal hypertension develop, resulting in splenomegaly and variceal formation. Myeloproliferative neoplasms (MPN) are the most frequent acquired etiology of EHPVO. These conditions put pregnant women at increased risk of vascular complications, including venous thrombosis, occlusion of the placental circulation, and variceal bleeding. In this report, we present a 36-year-old pregnant woman with chronic, anticoagulated EHPVO secondary to latent MPN who developed severe intrauterine growth restriction and had cesarean section at 32+1 weeks for increased umbilical doppler resistance and breech presentation. The article will emphasize outcome and management of pregnancies complicated by chronic EHPVO, portal hypertension, and MPN.